The Effect Of Rotational Plyometric Training Methods On The Smash Accuracy Of Volleyball Extracurricular Students - Reka Diah Pratiwi; Fajar Ari Widiyatmoko; Pandu Kresnapati (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Smashing is an important technique in volleyball. However, the accuracy of smashing remains a challenge for students in volleyball extracurricular activities. Muscle strength plays an important role in improving volleyball smashing skills. For this reason, core rotation plyometric exercises were chosen to improve smashing accuracy because they can increase muscle power. This study used a quasi-experimental method with a two-group pretest-posttest design, using an experimental group and a control group as a comparison. This study was conducted at MTS Sultan Fattah Gaji with a population of 8 students participating in volleyball extracurricular activities. The research sample used purposive sampling. The training program was conducted for 4 weeks with 3 meetings per week. Data were collected using the Smash Attack Test instrument and analyzed using a t-test with a significance level of 0.05. The results of the study concluded that there was no significant effect of core rotation plyometric training on the accuracy of volleyball smashes, with a mean value of -3.250, a t-value of -2.030, and a p-value of 0.135. Thus, p = 0.135 > 0.05, so H0 is accepted and H1 is rejected. Although there was an improvement from the pretest to the posttest, it was not strong enough to indicate a significant difference